Crushing behaviors of unidirectional carbon fiber reinforced plastic composites under dynamic bending and axial crushing loading. (June 2020) - Zhou, Guowei; Sun, Qingping; Fenner, Joel; Li, Dayong; Zeng, Danielle; Su, Xuming; Peng, Yinghong
Highlights: Dynamic crushing characteristics of UD CFRP composites are investigated under two loading types, i.e. dynamic three-point bending and axial crushing. Crushing processes with different layup orientations and velocities are compared by high speed camera and ultrasonic scan. A finite element model is established to analyze the contributions of different mechanisms to energy absorption at different conditions. Abstract: The dynamic crushing characteristics of unidirectional carbon fiber reinforced plastic composites under two loading types, dynamic three-point bending and axial crushing, are investigated by experiment and finite element simulation. Hat section samples with two different layup orientations are tested at various impact velocities to investigate its effects. The experiment results show that delamination plays a critical role in dynamic bending deformation. Different layup orientations lead to similar crushing bending behaviors, but remarkable variations in delamination pattern evolutions. In contrast, layup orientation exerts more significant effects on failure modes and energy absorption in axial crushing. A finite element model with multiple layers of thick shell element and cohesive element is established, and simulations are performed for both dynamic three-point bending and axial crushing. The model can capture the crushing behaviors in the two loading types reasonably well. The damage evolution and energy absorption through various mechanisms at different loading conditions are discussed.